Factors influencing market entry modes for outward Hong Kong foreign direct investments. - Ho, Yuen Peng. (2008)
This study explores the possible determinants affecting entry mode decisions on outward Foreign Direct Investments (FDI) in Hong Kong. Hypotheses are tested using data taken from 33 Hong Kong firms within a scope of 21 years - from Year 1980 to 2001.